Psychological Well-Being and Resilience of Slovenian Students During the COVID-19 Pandemic - ROPRET Nina; KOŠIR Urška; ROŠKAR Saška; KLOPČIČ Vito; VRDELJA Mitja (Sciendo, 2023)
Students' mental health is recognised as an important public health issue, and the strict measures and many changes resulting from the COVID-19 pandemic may have exacerbated this. The aims of the study were thus to explore psychological well-being among university students in Slovenia during the beginning of the second lockdown, and to assess associations among their psychological well-being, demographic characteristics, presence of a chronic health condition, and resilience.